A Novel High Step-Up DC-DC Converter with Coupled Inductor and Switched Clamp Capacitor Techniques for Photovoltaic Systems - Yong-Seng Wong; Jiann-Fuh Chen; Kuo-Bin Liu; Yi-Ping Hsieh (Energies, 2017)
In this study, a novel high step-up DC-DC converter was successfully integrated using coupled inductor and switched capacitor techniques. High step-up DC-DC gain was achieved using a coupled inductor when capacitors charged and discharged energy, respectively. In addition, energy was recovered from the leakage inductance of the coupled inductor by using a passive clamp circuit. Therefore, the voltage stress of the main power switch was almost reduced to 1/7 Vo (output voltage). Moreover, the coupled inductor alleviated the reverse-recovery problem of the diode. The proposed circuit efficiency can be further improved and high voltage gain can be achieved. The operation principle and steady-state analysis of the proposed converter were discussed. Finally, a hardware prototype circuit with input voltage of 24 V, output voltage of up to 400 V, and maximum power of 150 W was constructed in a laboratory; the maximum efficiency was almost 96.2%.